Comparison ofPost‐mortemMass Changes in Myosin Heavy Chain and Textural Characteristics amongOncorhynchus mykiss(Walbaum, 1972),Salmo trutta fario(Linnaeus, 1758) andSalvelinus fontinalis(Mitchill, 1814) - Çırak, Sait; Taştan, Yiğit; Sönmez, Adem Yavuz (Wiley, 2019)
In this study, post‐mortem myofibril proteins change in myosin heavy chain (MHC) mass using sodium dodecyl sulphate‐polyacrylamide gel electrophoresis (SDS‐PAGE), texture properties such as hardness, stickiness, cohesiveness, elasticity, chewiness, gumminess and stress relaxation test parameters (Fmax, Fmin and Fmax‐Fmin) were determined and compared on the days 0, 3, 6 and 9 in three different trout species (Oncorhynchus mykiss, Salmo trutta fario and Salvelinus fontinalis). In terms of texture properties, post‐mortem hardness, cohesiveness, elasticity, chewiness and gumminess were decreased day by day, whereas stickiness, Fmax, Fmin and Fmax‐Fmin were significantly increased (p < .05). According to SDS‐PAGE results, a decreased value on MHC was determined (p < .05). Texture properties and SDS‐PAGE results were found different among groups (p < .05). Correlation between chewiness, gumminess, MHC and hardness; between chewiness and gumminess; between Fmin, Fmax‐Fmin and Fmax; between Fmin and Fmax‐Fmin were significant. As a result of the study, S. fontinalis exhibited least deterioration in comparison with other species and it was determined that SDS‐PAGE results and texture properties support each other.